Posttreatment Low‐Risk Drinking as a Predictor of Future Drinking and Problem Outcomes Among Individuals with Alcohol Use Disorders. (24th July 2012) - Kline‐Simon, Andrea H.; Falk, Daniel E.; Litten, Raye Z.; Mertens, Jennifer R.; Fertig, Joanne; Ryan, Megan; Weisner, Constance M.
Abstract : Background: Treatment for alcohol disorders has traditionally been abstinence‐oriented, but evaluating the merits of a low‐risk drinking outcome as part of a primary treatment endpoint is a timely issue given new pertinent regulatory guidelines. This study explores a posttreatment low‐risk drinking outcome as a predictor of future drinking and problem severity outcomes among individuals with alcohol use disorders in a large private, not for profit, integrated care health plan. Methods: Study participants include adults with alcohol use disorders at 6 months ( N  = 995) from 2 large randomized studies. Logistic regression models were used to explore the relationship between past 30‐day drinker status at 6 months posttreatment (abstinent [66%], low‐risk drinking [14%] defined as nonabstinence and no days of 5+ drinking, and heavy drinking [20%] defined as 1 or more days of 5+ drinking) and 12‐month outcomes, including drinking status and Addiction Severity Index measures of medical, psychiatric, family/social, and employment severity, controlling for baseline covariates. Results: Compared to heavy drinkers, abstinent individuals and low‐risk drinkers at 6 months were more likely to be abstinent or low‐risk drinkers at 12 months (adj. ORs = 16.7 and 3.4, respectively; p  < 0.0001); though, the benefit of abstinence was much greater than that of low‐risk drinking. Compared to heavy drinkers, abstinent and low‐risk drinkers were similarly associated with lower 12‐month psychiatric severity (adj. ORs = 1.8 and 2.2, respectively, p  < 0.01) and family/social problem severity (adj. OR = 2.2; p  < 0.01). While abstinent individuals had lower 12‐month employment severity than heavy drinkers (adj. OR = 1.9; p  < 0.01), low‐risk drinkers did not differ from heavy drinkers. The drinking groups did not differ on 12‐month medical problem severity. Conclusions: Compared to heavy drinkers, low‐risk drinkers did as well as abstinent individuals for many of the outcomes important to health and addiction policy. Thus, an endpoint that allows low‐risk drinking may be tenable for individuals undergoing alcohol specialty treatment.